2015
DOI: 10.1021/acs.nanolett.5b03451
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Electromechanics To Measure Thermal Conductivity, Expansion, and Interfacial Losses

Abstract: We study the effect of localized Joule heating on the mechanical properties of doubly clamped nanowires under tensile stress. Local heating results in systematic variation of the resonant frequency; these frequency changes result from thermal stresses that depend on temperature dependent thermal conductivity and expansion coefficient. The change in sign of the linear expansion coefficient of InAs is reflected in the resonant response of the system near a bath temperature of 20 K. Using finite element simulatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…We also find negligible contributions from within both the high and low temperature regimes, which indicates that losses due to physisorbed species, for example, are negligible. Additionally, prior works on InAs nanowires 27 have demonstrated that energy dissipation due to clamping related losses results in a total measured dissipation on the order of 10 −4 at low temperatures, which is consistent with our results that Q −1 ( T ) ~  ~ 10 −4 at T  = 4.4 K (additional detailed information regarding the data analysis can be found in the Supporting Information). The results for few-layer MoS 2 NEMS are strikingly different than the theoretical predictions for the dominant loss mechanisms in single layer graphene 21 (which predict to dominate) and semiconductor resonators with micron-scale thickness 28 (which show that thermoelastic loss dominates).…”
Section: Resultssupporting
confidence: 92%
“…We also find negligible contributions from within both the high and low temperature regimes, which indicates that losses due to physisorbed species, for example, are negligible. Additionally, prior works on InAs nanowires 27 have demonstrated that energy dissipation due to clamping related losses results in a total measured dissipation on the order of 10 −4 at low temperatures, which is consistent with our results that Q −1 ( T ) ~  ~ 10 −4 at T  = 4.4 K (additional detailed information regarding the data analysis can be found in the Supporting Information). The results for few-layer MoS 2 NEMS are strikingly different than the theoretical predictions for the dominant loss mechanisms in single layer graphene 21 (which predict to dominate) and semiconductor resonators with micron-scale thickness 28 (which show that thermoelastic loss dominates).…”
Section: Resultssupporting
confidence: 92%
“…Considerable effort has been devoted to developing mechanical resonators based on low-dimensional materials, such as carbon nanotubes 1 2 3 4 5 6 7 8 9 10 11 12 , semiconducting nanowires 13 14 15 16 17 18 19 20 21 22 , graphene 23 24 25 26 27 28 29 and monolayer semiconductors 30 31 32 . The specificity of these resonators is their small size and their ultra-low mass, which enables sensing of force and mass with unprecedented sensitivities 7 10 .…”
mentioning
confidence: 99%
“…This fabrication method has several advantages compared with previous ones. Compared with the method reported in a previous study, where NWs are scattered on the substrate before its patterning or metal deposition, our method allows precise control of the NW position. Although the method using PDMS stamps to transfer NWs has a similar high accuracy, the stamps need to contact the NWs directly, so the interactions among the stamps, NWs, and substrate should be carefully controlled.…”
Section: Introductionmentioning
confidence: 99%